In Vitro Selection of Cancer Cell-Specific Molecular Recognition Elements from Amino Acid Libraries - Ryan M. Williams; Letha J. Sooter (Journal of Immunology Research)
Differential cell systematic evolution of ligands by exponential enrichment (SELEX) is an in vitro selection method for obtaining molecular recognition elements (MREs) that specifically bind to individual cell types with high affinity. MREs are selected from initial large libraries of different nucleic or amino acids. This review outlines the construction of peptide and antibody fragment libraries as well as their different host types. Common methods of selection are also reviewed. Additionally, examples of cancer cell MREs are discussed, as well as their potential applications.